Welfare economics : an interpretive history - McCain, Roger A. (Abingdon, Oxon ; New York, NY : Routledge, 2019)
Although it was an important specialization in economics in the mid-twentieth century, welfare economics has received less attention in the twenty-first century. This book explores the history of welfare economics, with a view to explaining its rise and subsequent decline. Drawing on both philosophy and economics, this book offers a new and original perspective on the history of welfare economics, starting with Pigou and charting the trajectory of applied and theoretical welfare economics throughout the twentieth century. This book will be of interest to students and researchers of philosophy, economics and history of economic thought.
OCLC-licensed vendor bibliographic record.
Keywords: Welfare economics -- History; BUSINESS & ECONOMICS / Economics / General; BUSINESS & ECONOMICS / Reference; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Economics / Theory